Ownership and Solvency of (Re)Insurance Companies: An Indonesian Climate-Based Insurance Study - Etikah Karyani; Rivan Dwi Aghnitama (Universitas Pasundan, 2024)
Despite the urgency of COVID-19, insurance companies are facing a slower-moving global crisis, namely climate change. This paper aims to investigate how corporate ownership affects the solvency of (re)insurance companies. It also analyses how climate-based insurance products, and the COVID-19 pandemic period differentiate these effects. The quantitative approach uses company accounting data throughout 2016-2022 and solvency is measured by risk-based capital (RBC). The findings show that for climate change-based (re)insurance companies, the larger the foreign-owned company, the higher the RBC level. Meanwhile, there is no difference in the effect of government and non-government owned insurance companies on their RBC. Another finding found that foreign ownership has a significant effect on the RBC of general insurance companies during the COVID-19 pandemic, while there is no relationship between the two during normal conditions. This research is expected to encourage the development and sustainability of climate change-based insurance, as well as input for financial regulators.